The characteristics of some Xhosa dramas - Sirayi, Mziwoxolo (Rhodes University, Faculty of Humanities, School of Languages, 1993)
This study aims at highlighting some crucial aspects of Xhosa drama. These aspects are of great significance for the understanding of Xhosa drama. It also aims to historicize and contextualize examinations of traditional Xhosa drama and modern Xhosa drama.
Keywords: African literature -- Criticism and interpretation; Xhosa drama -- History and criticism